A-site cation off-centering contribution on ferroelectricity and piezoelectricity in pseudo-cubic perovskite structure of Bi-based lead-free piezoelectrics. (December 2021) - Kim, Sangwook; Nam, Hyunwook; Fujii, Ichiro; Ueno, Shintaro; Moriyoshi, Chikako; Kuroiwa, Yoshihiro; Wada, Satoshi
Abstract: The origin of the significantly large piezoelectricity and ferroelectricity was investigated in the 0.67BiFeO3 –0.33BaTiO3 ceramics. The crystal structure of 0.67BiFeO3 –0.33BaTiO3, identified using the Rietveld method, suggested a cubic structure at 950 K and a rhombohedral structure at 300 K with small lattice distortion 89.94(4)°, which is close to 90° of cubic structure. Despite the small lattice distortion at 300 K, significantly large piezoelectricity and ferroelectricity was observed in the 0.67BiFeO3 –0.33BaTiO3, which is associated Bi ion off-centering. The Bi 3+ ions were off-centered from the corner of the Ba 2+ position along the 〈100〉 directions at 300 K, occupying three equivalent neighboring sites in the [100], [010], and [001] directions. The occupancies of Bi ions could be changed, and partially ordered along the applied electric field direction. The off-centered Bi ions are attributed to the ferroelectricity and piezoelectricity in non-centrosymmetry structure with a small lattice distortion, i.e., pseudo-cubic structure, due to partial ordering under the electric field. Graphical abstract: Image, graphical abstract